2022
DOI: 10.3390/antibiotics11121767
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Antibiotics and Neurodevelopmental Disorders: Could Probiotics Modulate the Gut–Brain Axis?

Abstract: In order to develop properly, the brain requires the intricate interconnection of genetic factors and pre-and postnatal environmental events. The gut–brain axis has recently raised considerable interest for its involvement in regulating the development and functioning of the brain. Consequently, alterations in the gut microbiota composition, due to antibiotic administration, could favor the onset of neurodevelopmental disorders. Literature data suggest that the modulation of gut microbiota is often altered in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 232 publications
0
8
0
Order By: Relevance
“…The dual genetic and environmental nature characterizing ASDs represent the main obstacle to the search for effective therapies 52 . However, many pharmacological therapeutic approaches have been developed to modulate UPR effectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dual genetic and environmental nature characterizing ASDs represent the main obstacle to the search for effective therapies 52 . However, many pharmacological therapeutic approaches have been developed to modulate UPR effectors.…”
Section: Discussionmentioning
confidence: 99%
“…The dual genetic and environmental nature characterizing ASDs represent the main obstacle to the search for effective therapies. 52 However, many pharmacological therapeutic approaches have been developed to modulate UPR effectors. Our group has previously shown that the retention of R451C NLGN3 causes ER stress and the activation of the UPR both in vitro and in vivo, which is correlated to neurotransmission alterations in the cerebellum.…”
Section: Generation Of Neural Staminal Progenitor Cultures From Adult...mentioning
confidence: 99%
“…45 Antibiotic exposure can disrupt the prenatal environment, potentially leading to neurodevelopmental changes that subsequently lead to ASD symptoms. 46 The potential gender differences between the effects of Tetracycline exposure and the risk of ASD symptoms remain unsolved. In our study, we found that Tetracycline exposure in the first and third trimesters was associated with an increased risk of ASD symptoms in boys but not in girls.…”
Section: Discussionmentioning
confidence: 99%
“…The fetal brain is particularly sensitive to ambient stimuli that affect the development of the central nervous system during the first and third trimesters . Antibiotic exposure can disrupt the prenatal environment, potentially leading to neurodevelopmental changes that subsequently lead to ASD symptoms . The potential gender differences between the effects of Tetracycline exposure and the risk of ASD symptoms remain unsolved.…”
Section: Discussionmentioning
confidence: 99%
“…Preterm, particularly veryto-extreme preterm infants, are even more susceptible to these drugs than full-term infants [26][27][28][29]. Antibiotics (mainly broad-spectrum antibiotics) can interfere with brain development [30][31][32], for example, increasing the risk of severe mental disorders later on as adults [33,34]. Moreover, Slykerman et al's research has linked the use of antibiotics in the first year of life to later neurocognitive impacts in children, such as anxiety and depression [35].…”
Section: But Why Is It Essential To Study the Factors Associated With...mentioning
confidence: 99%